2001
DOI: 10.1016/s1097-2765(01)00357-4
|View full text |Cite
|
Sign up to set email alerts
|

BCR/ABL Regulates Mammalian RecA Homologs, Resulting in Drug Resistance

Abstract: RAD51 is one of six mitotic human homologs of the E. coli RecA protein (RAD51-Paralogs) that play a central role in homologous recombination and repair of DNA double-strand breaks (DSBs). Here we demonstrate that RAD51 is important for resistance to cisplatin and mitomycin C in cells expressing the BCR/ABL oncogenic tyrosine kinase. BCR/ABL significantly enhances the expression of RAD51 and several RAD51-Paralogs. RAD51 overexpression is mediated by a STAT5-dependent transcription as well as by inhibition of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
327
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 313 publications
(360 citation statements)
references
References 38 publications
26
327
5
Order By: Relevance
“…Antibodies recognizing specifically the phosphorylated human RAD51 (either at Tyr-54 or Tyr-315) were generated by immunization of rabbit with the ovalbumin (OVA)-conjugated peptides (NeoMPS, France): the phosphopeptide TVEAVAY(PO 3 H 2 )APKKELINIKGIC was used to generate the antibody recognizing RAD51 phosphorylated at Tyr-54 and the phosphopeptide KIY(PO 3 H 2 )DSPCLPEAEAMFY for antibody recognizing RAD51 phosphorylated at Tyr-315. The antibodies were purified by using affinity chromatography with on Sulfolink gels [9] conjugated with the corresponding phosphorylated and unphosphorylated peptides, as described by the manufacture. Rabbit antihuman RAD51 antibody (a gift of Dr. Akira Shinohara) was used for RAD51 focus detection and immunoblot analysis as a primary antibody.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibodies recognizing specifically the phosphorylated human RAD51 (either at Tyr-54 or Tyr-315) were generated by immunization of rabbit with the ovalbumin (OVA)-conjugated peptides (NeoMPS, France): the phosphopeptide TVEAVAY(PO 3 H 2 )APKKELINIKGIC was used to generate the antibody recognizing RAD51 phosphorylated at Tyr-54 and the phosphopeptide KIY(PO 3 H 2 )DSPCLPEAEAMFY for antibody recognizing RAD51 phosphorylated at Tyr-315. The antibodies were purified by using affinity chromatography with on Sulfolink gels [9] conjugated with the corresponding phosphorylated and unphosphorylated peptides, as described by the manufacture. Rabbit antihuman RAD51 antibody (a gift of Dr. Akira Shinohara) was used for RAD51 focus detection and immunoblot analysis as a primary antibody.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the oncogenic form of c-ABL fusion kinase (BCR/ABL) has been shown to enhance RAD51 expression and to phosphorylate it on Tyr-315, resulting in resistance to drugs such as cisplatin and mitomycin C [9]. On the other hand, we have shown that arg -/-(ARG is the only other known member of the c-ABL family) and atm -/-DT40 chicken B cells show a mild impairment in RAD51 focus formation and HRR capacity [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, expression of anti-oxidative scavengers are under the control of STAT5, illustrating the interplay between JAK2 and STAT5 in balancing ROS action [117,118]. RAD51 members are conserved down to the E. coli RecA proteins and they are essential for DNA repair, which is downstream of cytokine- or TK-STAT signaling in mammalian cells [119,120]. However, the link between a hyperactive JAK-STAT pathway, TP53*, and mutated ATM/CHK2 is poorly understood.…”
Section: Targets In Ptcl and Driver Mutationsmentioning
confidence: 99%
“…The first role is stimulation of signaling pathways, which contribute to malignant transformation, including proliferation in the absence of growth factors, protection from apoptosis in the absence of external survival factors and invasion (Kolibaba and Druker, 1997;Liu et al, 2000;Cross and Reiter, 2002;Arlinghaus and Sun, 2004). The second role of FTKs in hematological malignancies is the modulation of responses to DNA damage, rendering cells resistant to genotoxic therapies and causing genetic instability (Alimena et al, 1987;Kelman et al, 1989;Laneuville et al, 1992;Bedi et al, 1995;Nishii et al, 1996;Amarante-Mendes et al, 1998;Dubrez et al, 1998;Villamor et al, 1999;Honda et al, 2000;Salloukh and Laneuville, 2000;Sercan et al, 2000;Aoki et al, 2001;Greenland et al, 2001;Slupianek et al, 2001).…”
Section: Consequences Of Ftks Expressionmentioning
confidence: 99%